Pelatihan Pembuatan Sabun dengan Bahan Minyak Kelapa di Desa Kalasey II Kecamatan Mandolang, Kabupaten Minahasa: Training in Making Soap Using Coconut Oil in Kalasey II Village, Mandolang, Minahasa - Rindengan, Elvie Rifke; Maramis, Rilyn Novita; Suleman, Nurningsih; Nahor, Evelina Maria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Improving community welfare can be done by providing skills training for the community and encouraging entrepreneurial spirit. Training in making soap with coconut oil was conducted in Kalasey II Village, Mandolang District. Minahasa is known as one of the coconut producers. Several UMKM in Minahasa have processed coconuts into pure coconut oil. The people of Kalasey II Village who have home businesses in the form of UMKM are still very few. The woman who are mostly active at home can be encouraged to use their free time to create entrepreneurship so that they can get additional income. The purpose of implementing this activity is to provide knowledge and motivation to become entrepreneurs for the community through making soap to increase family income. Training activities are carried out by explaining the materials and tools used, and a demonstration of making soap to packaging. The soap produced can be used for family needs and as a business opportunity to make souvenirs from soap.